2008
DOI: 10.1242/jeb.003145
|View full text |Cite
|
Sign up to set email alerts
|

The Frank–Starling mechanism in vertebrate cardiac myocytes

Abstract: SUMMARY The Frank–Starling law of the heart applies to all classes of vertebrates. It describes how stretch of cardiac muscle, up to an optimum length, increases contractility thereby linking cardiac ejection to cardiac filling. The cellular mechanisms underlying the Frank–Starling response include an increase in myofilament sensitivity for Ca2+, decreased myofilament lattice spacing and increased thin filament cooperativity. Stretching of mammalian, amphibian and fish cardiac myocytes reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
111
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 85 publications
5
111
0
4
Order By: Relevance
“…This elevated sensitivity of the fish hearts to the Starling response, well documented in both temperate eurytherm and cold-adapted teleosts (gilthead seabream, Icardo et al 2005;eel, Imbrogno et al 2001;icefish, Tota et al 1991), has been in part attributed to a greater myocardial extensibility of the highly trabeculate fish heart, coupled to a maintained increase in myofilament Ca 2þ sensitivity over a large range of sarcomere lengths (Di Maio & Block 2008;Shiels & White 2008).…”
Section: Introductionmentioning
confidence: 91%
“…This elevated sensitivity of the fish hearts to the Starling response, well documented in both temperate eurytherm and cold-adapted teleosts (gilthead seabream, Icardo et al 2005;eel, Imbrogno et al 2001;icefish, Tota et al 1991), has been in part attributed to a greater myocardial extensibility of the highly trabeculate fish heart, coupled to a maintained increase in myofilament Ca 2þ sensitivity over a large range of sarcomere lengths (Di Maio & Block 2008;Shiels & White 2008).…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, like muscles from mdm mice, cardiac myocytes are predicted to lack binding of N2A titin to the thin filaments. Cardiac myocytes of rats and mice exhibit no plateau in active force [46,47]. By contrast, cardiac myocytes from trout express the larger N2BA isoform, which includes both N2A and N2B isoforms, and is therefore predicted to exhibit Ca 2þ -dependent binding to thin filaments.…”
Section: Ca 21 -Dependent N2a -Actin Interactions Contribute To Lengtmentioning
confidence: 99%
“…This differs from mammals, which, for the most part, modulate cardiac output via larger changes in heart rate than stroke volume. These comparisons suggest a shift in the role of volume (and so myocardial stretch) in the regulation of cardiac output during vertebrate evolution (Burggren et al, 1997;Shiels and White, 2008). Indeed, we have recently shown that the fish heart is specialized for large extensions during diastolic filling and for active tension development during systolic emptying from a wide range of lengths (Patrick et al, 2010b).…”
Section: Introductionmentioning
confidence: 96%
“…It is surprising that the SFR has been largely ignored in nonmammalian myocardium, as non-mammalian vertebrates in general, and fish in particular, are known to be exquisitely sensitive to cardiac stretch (Farrell, 1991;Shiels et al, 2006;Shiels and White, 2008). Rainbow trout (Oncorhynchus mykiss) modulate their cardiac output primarily via changes in stroke volume, and can increase stroke volume by up to 300% during strenuous activity with little change in heart rate (Farrell and Olson, 2000).…”
Section: Introductionmentioning
confidence: 99%